EPCT-04. Stereotactic biopsy split-course radiation therapy for diffuse midline glioma of the pons (SPORT-DMG): Early phase II enrolling clinical trial. (3rd June 2022) - Cunningham, Danielle; Schwartz, Jonathan; Guerin, Julie; Johnson, Derek; Khatua, Soumen; Laack, Nadia; Ahmed, Safia; Silvera, Victoria Michelle; Brinkmann, Debra; Pafundi, Deanna; Keating, Gesina; Raghunathan, Aditya; et al.
Abstract: Diffuse midline glioma (DMG) of the pons remains the leading cause of death among pediatric patients with brain tumors, despite numerous attempts to intensify treatment. While standard treatment includes 54Gy in 30 fractions of radiation over six weeks of time, nearly all patients progress within the treatment field, and many experience symptomatic radionecrosis with steroid dependence. Symptom improvement typically begins after 20Gy to the tumor. Both hypofractionation and reirradiation after recurrence have been found to be safe for patients with DMG. Our study aims to enroll patients with newly diagnosed pontine DMG aged >1 year (no maximum age), and collect molecular information about DMG via stereotactic biopsy, followed by a short 2 week course of 25Gy in 10 fractions of radiation, with volumes guided by MRI with tractography reconstruction and FDOPA PET radiotracer uptake. Patients are followed closely and can complete the 25Gy in 10 fraction radiation course up to 3 times total for meeting radiographic and clinical progression criteria. Our primary endpoint is to estimate the time to progression from diagnosis to after receiving the second 25Gy course, and to compare this to the historical 7 month standard from diagnosis to progression after one 54Gy course. We aim to improve the time interval where patients are asymptomatic at home while minimizing time receiving daily treatments. Other endpoints will include the patient quality of life, caregiver quality of life, PFS intervals after each course, overall survival, and toxicity.